2003
DOI: 10.1248/cpb.51.58
|View full text |Cite
|
Sign up to set email alerts
|

Naucleamides A-E, New Monoterpene Indole Alkaloids from Nauclea latifolia.

Abstract: Five new monoterpene indole alkaloids, naucleamides A-E (1-5), were isolated from the bark and wood of Nauclea latifolia, and the structures and relative stereochemistry were elucidated from the spectroscopic data. Naucleamide E (5) is a unique monoterpene indole alkaloid possessing a pentacyclic ring system with an amino acetal bridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 8 publications
0
64
0
2
Order By: Relevance
“…98 (H-14a) and 2.10 (H-14b) suggested that the secologanin unit was attached to the C-3 carbon, as reported for other similar monoterpenoid alkaloids. 10 This suggestion was supported by the 13 C NMR spectrum along with the distortionless enhancement by polarization transfer (DEPT 135), that revealed 26 carbons atoms corresponding to three methylenes, one oxymethylene and one vinylidene, three methines, two hemiketal methynes and four oxymethines, six monohydrogenated sp 2 carbons, and six non-hydrogenated carbons. However, the confirmation of the structure of 1 was supported by the HMQC and HMBC (heteronuclear multiple quantum coherence and heteronuclear multiple bond coherence, respectively) experiments, that revealed the unequivocal assignments of its NMR data.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…98 (H-14a) and 2.10 (H-14b) suggested that the secologanin unit was attached to the C-3 carbon, as reported for other similar monoterpenoid alkaloids. 10 This suggestion was supported by the 13 C NMR spectrum along with the distortionless enhancement by polarization transfer (DEPT 135), that revealed 26 carbons atoms corresponding to three methylenes, one oxymethylene and one vinylidene, three methines, two hemiketal methynes and four oxymethines, six monohydrogenated sp 2 carbons, and six non-hydrogenated carbons. However, the confirmation of the structure of 1 was supported by the HMQC and HMBC (heteronuclear multiple quantum coherence and heteronuclear multiple bond coherence, respectively) experiments, that revealed the unequivocal assignments of its NMR data.…”
Section: Resultsmentioning
confidence: 89%
“…11, 2011 the typical aromatic signals at d 7.22 (td, J 7.4 and 1.0 Hz, H-10), 7.26 (td, J 7.4 and 1.3 Hz, H-11), 7.45 (dd, J 7.4 and 1.3 Hz, H-9), 8.15 (dd, J 7.4 and 1.0 Hz, H-12), besides the two methylenes at d 3.10 (t, J 5.5 Hz, 2H-5) and 2.70 (t, J 5.4 Hz, 2H-6). 10 The 1 H NMR spectrum also showed signals relative to an iridoid unit related to a secologanin moiety due to the signals of the olefinic hydrogen at d 5.85 (ddd, J 17.6, 10.0 and 7.6 Hz, H-19), the vinylidene group at -19). The strong correlations observed for the methine hydrogen at d 4.20 (H-3) and the methylene group at d 1.98 (H-14a) and 2.10 (H-14b) suggested that the secologanin unit was attached to the C-3 carbon, as reported for other similar monoterpenoid alkaloids.…”
mentioning
confidence: 98%
“…Two novel tetrahydro-ß-carboline monoterpene alkaloid glycosides, naucleaorine and epimethoxy-naucleaorine, isolated by chloroform from the dried stem of N. latifolia, strictosidine lactam, and oleanolic acid showed moderate in vitro activities against Plasmodium falciparum. 4 The fact that aqueous fraction showed the highest chemosuppressive effect when compared with others suggests that the active ingredients of this plant responsible for its antimalarial activity may be localized here. The antiplasmodial activities of Nauclea latifolia extract and its fractions as observed in this study may, therefore, have resulted from one or more of these mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…These secondary metabolites could have elicited the observed antiplasmodial activity either singly or in synergy with each other. 4 Alkaloids have been known to show antimalarial properties by blocking protein synthesis in Plasmodium falciparum. 23 Saponin, fl avonoids and tannins have been suggested to act as primary antioxidant or free radicals scavengers that can counteract the oxidative damage induced by the malaria parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation